2008
DOI: 10.1016/j.jcf.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the use and interpretation of cystic fibrosis mutation analysis in clinical practice

Abstract: It is often challenging for the clinician interested in cystic fibrosis (CF) to interpret molecular genetic results, and to integrate them in the diagnostic process. The limitations of genotyping technology, the choice of mutations to be tested, and the clinical context in which the test is administered can all influence how genetic information is interpreted. This paper describes the conclusions of a consensus conference to address the use and interpretation of CF mutation analysis in clinical settings. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
465
3
48

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(529 citation statements)
references
References 143 publications
(166 reference statements)
13
465
3
48
Order By: Relevance
“…Strom et al 7 advocate against adding these variants to CF panels, stating that detection of D1152H and L206W during carrier screening may increase the rate of pregnancy termination among parents who fear having a child with classic CF, not to mention inflating the mutation detection rate among Hispanic Americans. 7 It is acknowledged now in the literature that the D1152H variant belongs to both the CF-causing and CFTR-related disorder groups, [19][20][21] and, in conjunction with an established CF-causing mutation, it could still manifest as typical CF. 19,22 Burgel et al 23 studied 42 patients with D1152H mutations and reported that the variant, in conjunction with a CF-causing mutation, can cause significant pulmonary disease, albeit with longer survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strom et al 7 advocate against adding these variants to CF panels, stating that detection of D1152H and L206W during carrier screening may increase the rate of pregnancy termination among parents who fear having a child with classic CF, not to mention inflating the mutation detection rate among Hispanic Americans. 7 It is acknowledged now in the literature that the D1152H variant belongs to both the CF-causing and CFTR-related disorder groups, [19][20][21] and, in conjunction with an established CF-causing mutation, it could still manifest as typical CF. 19,22 Burgel et al 23 studied 42 patients with D1152H mutations and reported that the variant, in conjunction with a CF-causing mutation, can cause significant pulmonary disease, albeit with longer survival.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is acknowledged now in the literature that the D1152H variant belongs to both the CF-causing and CFTR-related disorder groups, [19][20][21] and, in conjunction with an established CF-causing mutation, it could still manifest as typical CF. 19,22 Burgel et al 23 studied 42 patients with D1152H mutations and reported that the variant, in conjunction with a CF-causing mutation, can cause significant pulmonary disease, albeit with longer survival. One of the authors of this article observed similar results (K.J.F., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Their decisions are based on expert consensus and best practice guidelines, and depend on the clinical indication in the case. [13][14][15][16] Two assessors independently evaluate genotypes and interpretation in the submitted reports. Results are also discussed during an assessment meeting.…”
Section: Context and Setting Of The Studymentioning
confidence: 99%
“…Interpretation could additionally be influenced by external factors such as the availability of best practice guidelines and publications. [13][14][15] Second, the presence in clinical reports of all investigated interpretation elements improved over the years. Two elements increased remarkably more (430%) than others: stating the need to test the parents of a CF patient to confirm homozygosity or compound heterozygosity (need for qualification of the genotype) and Interpretation in CF laboratory reports S Berwouts et al mentioning the possibility of testing the relatives.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR/ABCC7; MIM #602421) induce a wide spectrum of clinical phenotypes from classic CF characterized by pancreatic insufficiency and positive sweat chloride values, to milder forms of the disease with pancreatic sufficiency, to CFTR related disorders (CFTR-RDs), where a diagnosis of CF cannot be established because the individual does not meet standard diagnostic criteria (Farrell et al 2008;Castellani et al 2008). …”
mentioning
confidence: 99%